Publication of The Lithuanian Manuscript Heritage in Digital Space: Analysis of Digitized and Publicly Accessible Collections from The Technical Perspective - Gudinavičius, Arūnas (Knygotyra, 2011)
The paper identifies the already digitized and publicly accessible online manuscript heritage collections (websites) in Lithuania. The object of research was the quality of digitized manuscript heritage collections, i.e. any manuscripts collections, archives, sets presented in the form of a website, published and publicly available on the Internet. A correlation among good practice standards and international recommendations is analyzed. The analysis is based on the MINERVA quality principles for cultural heritage sites. It is concluded that the weakness of the Lithuanian websites is their maintaining and continuity, their strong sides being the quality of technological execution. The current situation is stated (compilers of current projects, the published and publicly available collections) and recommendations for the future projects are formulated.
Keywords: digital archive; manuscript heritage; quality criteria